2021
DOI: 10.1037/emo0001039
|View full text |Cite
|
Sign up to set email alerts
|

Never too late to plan: “Refocus on planning” as an effective way to lower symptoms and difficulties in emotion regulation during the COVID-19 first lockdown.

Abstract: Lockdowns during the COVID-19 pandemic have put people in stressful situations. Recent research showed elevated levels of anxiety and depression during this period, but no study has so far evaluated to what extent emotions and regulation difficulties were perceived by people as having changed with the lockdown. This was the major aim of the present study, together with investigating whether the emotion regulation strategy of "Refocus on planning" could be an effective strategy in this context. With a 1 time-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 115 publications
1
14
0
Order By: Relevance
“…Therefore, it is important that these treatments are available to students experiencing clinically significant OC symptoms as a result of the pandemic. Our findings also suggest that interventions aimed at improving emotion regulation (e.g., Affect Regulation Training [ART]; Berking, 2010 ; Berking et al, 2008 ) may weaken the association between COVID-19 impact and pathological outcomes.Accordingly, Sacchi and Dan-Glauser (2021) Accordingly, Sacchi and Dan-Glauser (2021) recently demonstrated that using adaptive coping strategies during the pandemic, specifically future-oriented planning (e.g., identify the necessary next steps to manage difficult events; Carver, Scheier, & Weintraub, 1989 ) may interrupt the emotion emergence process, and decrease both emotion regulation difficulties and internalizing symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important that these treatments are available to students experiencing clinically significant OC symptoms as a result of the pandemic. Our findings also suggest that interventions aimed at improving emotion regulation (e.g., Affect Regulation Training [ART]; Berking, 2010 ; Berking et al, 2008 ) may weaken the association between COVID-19 impact and pathological outcomes.Accordingly, Sacchi and Dan-Glauser (2021) Accordingly, Sacchi and Dan-Glauser (2021) recently demonstrated that using adaptive coping strategies during the pandemic, specifically future-oriented planning (e.g., identify the necessary next steps to manage difficult events; Carver, Scheier, & Weintraub, 1989 ) may interrupt the emotion emergence process, and decrease both emotion regulation difficulties and internalizing symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Refocus on planning is an adaptive strategy, and an earlier study showed that refocus on planning contributes to resilience in patients with depression and anxiety disorders [ 43 ]. A study conducted more recently also indicated that higher use of refocus on planning strategy is associated with more positive emotions and anxiety symptoms are lower only when more planning is adopted [ 44 ]. The finding of this study demonstrates that as the WMC gets lower, a refocus on planning strategy is used more against emotions which might be interpreted as being more in need of using a strategy when being low in terms of memory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of cognitive flexibility and cognitive emotion regulation scales also revealed positive correlations in the present study. Refocus on planning, an adaptive strategy, and a coping style which were found in previous research as being highly related to resilience, well-being, and higher use of refocus on planning as a cognitive emotion regulation strategy are associated with more positive emotions while also anxiety symptoms are lower only when more planning is adopted [ 44 , 53 ]. On the other hand, cognitive flexibility is defined as being aware of alternatives for a situation and also being willing to adapt to this situation as well as having self-efficacy against this adaptation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, reappraisal (an emotion regulation strategy) reduces anxiety and worries [ 74 , 75 ]. A recent study showed that emotion regulation strategies alleviate symptoms and difficulties, such as anxiety [ 76 ]. Thus, by enhancing one’s emotion regulation skills, employee career satisfaction might also benefit by reduced worries and anxiety, especially in a context such as the COVID-19 pandemic, where stress and worries are inevitable.…”
Section: Discussionmentioning
confidence: 99%